The Combination Of Ethics And Aesthetics With Regard To The Representation Of The Body In Culture - Żukowska, Dominika (Studia Theologica Varsaviensia, 2020)
The Combination Of Ethics And Aesthetics With Regard To The Representation Of The Body In Culture